2019
DOI: 10.3390/cancers11060784
|View full text |Cite
|
Sign up to set email alerts
|

Nerve Growth Factor Induces Proliferation and Aggressiveness in Prostate Cancer Cells

Abstract: Resistance to hormone therapy and disease progression is the major challenge in clinical management of prostate cancer (PC). Drugs currently used in PC therapy initially show a potent antitumor effects, but PC gradually develops resistance, relapses and spreads. Most patients who fail primary therapy and have recurrences eventually develop castration-resistant prostate cancer (CRPC), which is almost incurable. The nerve growth factor (NGF) acts on a variety of non-neuronal cells by activating the NGF tyrosine-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(60 citation statements)
references
References 90 publications
1
59
0
Order By: Relevance
“…Vimentin, a cytoskeleton protein, has been linked to initiation of the EMT. 23 A previous study reported that a specific N-cadherin antibody could inhibit EMT progression while simultaneously reducing tumor growth invasion and migration in PC. 24 In this study, we observed increased E-cadherin and diminished N-cadherin and Vimentin expression as a result of MLPH depletion, thus implying the expression of MLPH in the EMT of PC cells.…”
Section: Discussionmentioning
confidence: 99%
“…Vimentin, a cytoskeleton protein, has been linked to initiation of the EMT. 23 A previous study reported that a specific N-cadherin antibody could inhibit EMT progression while simultaneously reducing tumor growth invasion and migration in PC. 24 In this study, we observed increased E-cadherin and diminished N-cadherin and Vimentin expression as a result of MLPH depletion, thus implying the expression of MLPH in the EMT of PC cells.…”
Section: Discussionmentioning
confidence: 99%
“…To elucidate the relationship between DAB2 and tumor cells, cytokines, and the microenvironment surrounding the cancer cells, we need further experimentation. Recent reports have shown that nerve growth factor (NGF) promotes EMT in prostate cancer cells via activation of the NGF tyrosine kinase receptor, tropomyosin receptor kinase A [34]. Lastly, we had variations related to tumor injection, tumor measurement, and intratumoral administration that might affect the outcomes of our in vivo study.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, these researchers conclude that the interaction between AR and FlnA is a key event for FAK activation, and paxillin tyrosine phosphorylation in androgen-stimulated cells further reinforces the role of the AR/FlnA interaction in androgen-mediated motility. [95][96][97] In most cancers, the epithelial-mesenchymal transition (EMT) is a key event in metastasis. At the molecular level, the EMT is characterized by a decrease in the expression of epithelial markers, mainly E-cadherin, which is located on the cell surface of epithelial tissues, and an increase in the expression of mesenchymal markers, such as vimentin, a cytoskeleton protein associated with EMT initiation.…”
Section: Fak Is the First Signaling Molecule Of αVβ3 In The Cytoplasmmentioning
confidence: 99%